Prevalence and Factors Associated with Food Allergen Sensitization Detected by Skin Prick Testing in Congolese Children with Atopic Dermatitis: A Cross-Sectional Study of 102 Patients at the North Kivu Provincial Hospital, 2025 - Pascaline Ngolo Masudi; Seudjip Nono; Pierre Kitha Bitingo; Louis Kyembwa Mwindulwa; Desire Ndayazi Byemero; Stanis Wembonyama Okitotsho (European Scientific Journal, ESJ, 2026)
Background: Skin prick testing plays a key role in assessing allergic sensitization. However, its use remains limited in clinical practice in the Democratic Republic of Congo, particularly among children with atopic dermatitis. This study aimed to determine the prevalence of food allergen sensitization, as detected by skin prick testing, and to identify its associated factors among Congolese children with atopic dermatitis managed at the Provincial Hospital of North Kivu.Methods: A descriptive and analytical cross-sectional study was conducted, including 102 patients ranging in age from six months to fourteen years, all diagnosed with atopic dermatitis. Skin prick tests were performed in all participants to detect sensitization to food allergens. Testing was carried out using foods provided by parents or legal guardians that were suspected of being responsible for the observed dermatitis lesions. Data were recorded and analyzed using the Statistical Package for the Social Sciences (SPSS), version 27.Results: Among the 102 patients, 36 were sensitized to at least one food allergen, corresponding to a prevalence of 35.3%. Cow’s milk was the food most frequently suspected by parents to be responsible for atopic dermatitis lesions (53.9%). However, skin prick test results revealed a slightly different pattern, with sensitization most commonly observed to peanut (20.6%), African eggplant (16.7%), and cow’s milk (13.7%). Univariate analysis demonstrated a statistically significant association between food sensitization detected by skin prick testing and age under five years (p = 0.002), male sex (p < 0.001), urban residence (p = 0.004), and severe atopic dermatitis (p = 0.004). Multivariate analysis showed that early onset of atopic dermatitis markedly increased the risk of food sensitization. The risk was particularly high when dermatitis began before three months of age (adjusted OR = 28.558; 95% CI: 3.851–211.771; p = 0.001), between three and six months (adjusted OR = 70.344; 95% CI: 3.018–1639.768; p = 0.008), or between six and nine months (adjusted OR = 43.591; 95% CI: 1.848–1028.250; p = 0.019). Conversely, early introduction of complementary feeding before six months of age was associated with a protective effect (OR = 0.041; 95% CI: 0.006–0.269; p = 0.001).Conclusion: Congolese children with atopic dermatitis are frequently sensitized to certain food allergens, particularly peanut and African eggplant. This sensitization seems to be associated with multiple factors, including clinical characteristics as well as social and environmental determinants.